Characteristics and Pollution Contribution of the Internal Nitrogen Release From the Sediments in the Dahekou Reservoir in Inner Mongolia - Lu, Junping; Liu, Tingxi; Shi, Xiao Hong; Sun, Biao; Zhao, Shengnan (Frontiers in Environmental Science, 2022)
To clarify the influence of the changes in the overlying water environment on the internal nitrogen release from reservoir sediments in different seasons, the quantitative linear relationship between the intensity of the nitrogen release from the sediment and the environmental factors of the overlying water was established, and their contribution rate to the nitrogen pollution of the reservoir during different storage periods was investigated. In this study, the sediment samples were collected from the Dahekou Reservoir in the Xilingol League, and the orthogonal simulation experiments were conducted in the laboratory. The mathematical model, which was established using multiple linear regression methods, revealed the following. The order of the significance of the influences of the environmental factors on the nitrogen release from the sediments in the Dahekou Reservoir is water temperature (T) > dissolved oxygen (DO) > pH value > hydrodynamic force (K). The total nitrogen release flux from the sediments in the Dahekou Reservoir was 14.278 t/a in 2018, accounting for 27.91% of the total nitrogen (TN) pollution load input during the same period. In particular, in winter, the contribution rate of the nitrogen released from the sediments reached the highest level (57.06–63.26%), which was significantly higher than the river’s contribution to the total nitrogen pollution load of the reservoir. The nitrogen released from the sediments became the main source of nitrogen nutrients in the reservoir in the ice-sealed period.